Analisis Budaya Literasi pada Mata Pelajaran Sejarah Kebudayaan Islam untuk Meningkatkan Minat Belajar Peserta Didik Kelas VIII di MTsN 3 Padang Pariaman - Cania, Salsabila Rizka; Alfurqan, Alfurqan (YASIN, 2025)
The limited research on the implementation of literacy culture in the Sejarah Kebudayaan Islam (Islamic Cultural History) subject has become a critical concern, as it affects students' learning interest. This study aims to describe the implementation of literacy culture in SKI lessons, analyze its supporting and inhibiting factors, and identify the teaching strategies employed by educators. A qualitative method with a case study approach was used, involving eighth-grade students at MTsN 3 Padang Pariaman, selected through purposive sampling. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that literacy culture is implemented through routine activities such as reading textbooks for 10–15 minutes, group discussions, and summarizing tasks. Supporting factors include teacher commitment, a conducive learning environment, and institutional support from the madrasah, while obstacles encountered involve students forgetting to bring books, limited instructional time, and extensive lesson content. The teaching strategies employed comprise expository and cooperative strategies. These findings support school literacy theory and highlight that consistent literacy habits can enhance students’ active participation and learning interest. The implications of this study contribute to enriching the discourse on school-based literacy culture and offer practical recommendations for teachers to optimize literacy-based teaching strategies, while also opening avenues for further research on the impact of literacy culture on academic achievement in other subjects.